Difluorophosphoric Acid Generation and Crossover Reactions in LiNixCoyMnzO2 Cathodes Operating at High Voltage - Jayawardana, Chamithri; Rodrigo, Nuwanthi D.; Rynearson, Leah; Lucht, Brett L. (Journal of the Electrochemical Society, 2022)
Abstract Cycling lithiated metal oxides to high potential (>4.5 V vs Li) is of significant interest for the next generation of lithium ion batteries. However, cells cycled to high potential suffer from rapid capacity fade due to a combination of thickening of the anode solid electrolyte interphase (SEI) and impedance growth on the cathode. While transition metal catalysed degradation of the anode SEI has been widely proposed as a primary source of capacity loss, a related acid induced degradation of the anode SEI is proposed. A systematic investigation of LiNi0.5Co0.2Mn0.3O2, and LiNi0.8Co0.1Mn0.1O2 cathodes cycled to 4.2 and 4.6 V has been conducted and the oxidative generation of the strong acid difluorophosphoric acid (F2PO2H) has been quantified by solution nuclear magnetic resonance spectroscopy. Ex-situ surface analysis of the electrodes with X-ray photoelectron spectroscopy suggests that the generation of F2PO2H correlates with a thickening of the anode SEI and an increase in the fluorophosphate content of the SEI. Changes to the LiNi0.8Co0.1Mn0.1O2 surface for cells cycled to 4.6 V are also consistent with the generation of acidic species. There is good correlation between the concentration F2PO2H, anode SEI degradation and the capacity loss of the cells